Genotypic Variation in Responses of Cassava (Manihot esculenta Crantz) to Drought and Rewatering: Root System Development - Juvy Oliva Q. Subere; Dioscoro Bolatete; Reynaldo Bergantin; Andreu Pardales; Jedi Jim Belmonte; Algerico Mariscal; Rodrigo Sebidos; Akira Yamauchi (Plant Production Science, 2009)
Soil moisture condition is a major factor that affects root system development and thus, crop production. This study aimed to evaluate genotypic variations of cassava in root system structures and their responses to different soil moisture conditions by examining various root traits including production and elongation of adventitious roots and their laterals. Four pot experiments were conducted and different genotypes of various backgrounds were grown under well-watered, droughted, droughted to rewatered conditions. One field experiment was also conducted with selected genotypes till maturity. Results showed that substantial genotypic variations exist in root system structure, and the effects of the soil moistures were significant for most of the root traits. The principal component analysis (PCA) showed that the lateral root development mainly accounted for the variations in root system structure regardless of soil moisture conditions. The PCA on the differences between droughted and well-watered control, and droughted-rewatered and the control further indicated that the branching ability of adventitious roots was mainly responsible for the root system responses to drought as well as rewatering. Genotypic ranking in root system responses to drought was almost consistent among the pots and field experiments. Genotypicvariations in rooting depth were relatively small while those in horizontal spread were apparent in the field experiment.The ability to maintain adventitious root elongation under drought, resulting in relatively large horizontal spread of root system and to recover sharply from drought by lateral root branching may be related to good growth and yield performance under field.